A participatory and systemic training approach for IPC improvement in Nigerian health facilities. (30th September 2020) - Zocher, U; Okwor, T J; Dan-Nwafor, C; Yahya, D; Ita Ita, O; Saleh, M; Ogunniyi, A; Ihekweazu, C; Poggensee, G
Abstract: Background: Health care-associated infections (HAI) are one of the most common adverse events in care delivery and a major public health problem. A large percentage of HAI in hospitals are preventable through effective infection prevention and control (IPC) measures. IPC trainings for health care personnel based only on technical content do not lead to sustainable improvement of IPC standard precautions. To address this problem, the Nigeria Centre for Disease Control (NCDC) in collaboration with the Robert Koch Institute (RKI) developed a multimodal training approach to facilitate the transfer of IPC competences into working routine in Nigerian health facilities. Objectives: The training should foster the ability of health care workers to act and communicate participatory, analyze IPC problems systemically and to develop and perform tailored IPC activities in their health facilities. It should empower health care workers to initiate and promote sustainable IPC improvement locally. Results: We developed a participatory training approach which focusses on the relational and organizational dimension of IPC. It addresses the human and infrastructural factors for IPC compliance in daily working routine. A variety of training methods offers practice tools in communication, systemic thinking and team work, and allows experiencing a participatory attitude. The training program consists of two face to face workshops and an interjacent field project. 28 Health care workers of 14 health facilities in Lagos State participated the first implementation of the training program in 2018. The training evaluation showed the high relevance of the training to the HCW. The field projects showed that the participants could apply the participatory approach for IPC improvement. Conclusions: A participatory and systemic approach for IPC trainings enables health care workers to take action for IPC improvement locally. Key messages: We developed and implemented a participatory training approach that addresses the relational and organizational dimension of IPC. Health care workers took tailored actions for IPC improvement locally.